Fluorescent copolymer aggregate sensor for lithium chloride. Issue 15 (28th March 2023) - Wang, Hu; Jones, Leighton O.; Zhao, Tian; Hwang, Inhong; Lynch, Vincent M.; Khashab, Niveen M.; Schatz, George C.; Page, Zachariah A.; Sessler, Jonathan L.
Abstract : We report a copolymeric lithium chloride selective fluorescent sensor. No fluorescence change is seen upon the addition of NaCl, KCl, MgCl2, or CaCl2, while a fluorescence decrease is seen upon the addition of LiCl. Abstract : We report a copolymeric fluorescent sensor that is selective for lithium chloride. The two constituent polymers comprise pendent triphenylethylene (TPE) moieties for aggregate induced emission (AIE) along with either strapped-calix[4]pyrrole or secondary ammonium groups that drive aggregation via self-assembly upon polymer mixing. Addition of LiCl in acetonitrile disrupts the strapped-calix[4]pyrrole/secondary ammonium chloride salt host–guest crosslinks leading to disaggregation of the polymer chains and a decrease in TPE emission. The lack of AIE perturbation upon addition of NaCl, KCl, MgCl2 or CaCl2 provides for high selectivity for LiCl relative to potential interferants. This supramolecular dual polymer approach could serve as a complement to more traditional sensor systems.